Structuring and Implementing the Brazilian Academic Cloud: Strategy, Modelling, Challenges and Services - Ribeiro Filho, José Luiz; Nunes, Antônio Carlos Fernandes; Nobuyoshi Dos Santos Makino, Ricardo; Barreto Araújo, Gorgonio; Machado Leopoldino Martins, Graciela; De Oliveira Guimarães, Leandro Marcos (My University, 2015)
This paper presents an overview of the strategies currently adopted by some National Research and Education Networks (NREN) to implement and offer scientific cloud computing services. It describes the constraints, opportunities and the strategy chosen by the Brazilian NREN – Rede Nacional de Ensino e Pesquisa (RNP) to plan, deploy and operate cloud services to and in collaboration with Brazilian public universities and research institutes. The hybrid, community and federated strategy was chosen as the most flexible and suitable for the current Brazilian NREN operation and funding models. It describes the cloud services that are in production or in a pilot phase, their status and next steps planned. Cloud service planning, deployment and operation are discussed, the alternatives considered and the chosen options. At the end, the cloud services deployed by RNP are presented and discussed, considering the technologies and benefits to the academic community in Brazil.
Keywords: cloud strategies; scientific cloud; cloud services; research and education network; hybrid and community cloud; federated cloud